Coordinated control of three-phase AC and DC type EV–ESSs for efficient hybrid microgrid operations. (15th August 2016) - Rahman, Md Shamiur; Hossain, M.J.; Lu, Junwei
Highlights: A coordinated control is proposed for three-phase AC and DC type electric vehicles. A four-quadrant interlinking converter is designed for hybrid microgrid operations. Concurrent real irradiation data and commercial load profile are used for testing. Unbalanced scenario due to single-phase electric vehicle charging is considered. Improved AC and DC bus voltages and frequency regulations are achieved. Abstract: This paper presents a three-layered coordinated control to incorporate three-phase (3P) alternating current (AC) and direct current (DC) type electric vehicle energy storage systems (EV–ESSs) for improved hybrid AC/DC microgrid operations. The first layer of the algorithm ensures DC subgrid management by regulating the DC bus voltage and DC side power management. The second and third layer manages AC subgrid by regulating the AC bus voltage and the frequency by managing reactive and active power respectively. The multi-layered coordination is embedded into the microgrid central controller (MGCC) which controls the interlinking controller in between AC and DC microgrid and the interfacing controllers of the participating electric vehicles (EVs) and distributed generation (DG) units. The whole system is designed in MATLAB/SIMULINK® environment resembling the under construction microgrid at Griffith University, Australia. Extensive case studies are performed using real life irradiation data and commercial loads of the campus buildings. Impacts of homogeneous and heterogeneous single-phase EV charging are investigated to observe both balanced and unbalanced scenarios. Synchronization during the transition from the islanded to grid-tied mode is tested considering a contingency situation. From the comparative simulation results it is evident that the proposed controller exhibits effective, reliable and robust performance for all the cases.